Students' attitudes and awareness of the reference services at the Perpetual Help College of Laguna Library - Baccay, James Paul J.; Buenrostro, Juan Jr. C. (Quezon City : Institute of Library Science, University of the Philippines Diliman, 1996)
The study was conducted to determine the students' attitudes and awareness of the reference services at the Perpetual Help of Laguna (PHCL) College Library. It also assessed the library's reference services with the intention of arriving at measures towards improvement of the services at the PHCL Library. A total of 251 undergraduate students enrolled during the second semester of 1995-1996, served as respondents of the study. The findings revealed that sophomores were the frequent users of the reference services and that there was a very high awareness about the services (89 percent) among the respondents. Almost all of the respondents (79.7 percent) consulted the services for their class assignments and 41.8 percent for making their term paper. While the respondents were (89.6 percent) aware of the existence of the reference services, most of them only fairly knew about the available services (59.76 percent). Only 21.91 percent fully knew about the said services. The freshmen were more satisfied with their reference and information needs (75.51 percent) as compared to the other year levels who, almost half of them, do not find satisfaction in their reference and information needs. About 80.62 of the respondents sought assistance from the librarian or any support staff in their search for information and almost all of them were satisfied with the assistance provided to them. The services were rated from very satisfactory to good.
Vita.
Thesis (Bachelor of Library Science)--University of the Philippines Diliman
Keywords: Perpetual Help College of Laguna. Library; Reference services (Libraries) -- Philippines -- Laguna